2015
DOI: 10.1016/j.jcmgh.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiota and Liver Disease

Abstract: The leaky gut hypothesis links translocating microbial products with the onset and progression of liver disease, and for a long time was considered one of its major contributors. However, a more detailed picture of the intestinal microbiota contributing to liver disease started to evolve. The gut is colonized by trillions of microbes that aid in digestion, modulate immune response, and generate a variety of products that result from microbial metabolic activities. These products together with host-bacteria int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(136 citation statements)
references
References 117 publications
(209 reference statements)
3
129
0
4
Order By: Relevance
“…We further demonstrated that these CXCL10-enriched EVs are biologically active and are a very potent inducer of macrophage chemotaxis (23). In the current study, we extend these observations to show that the lipotoxic mediator LPC can activate macrophages, as well as potentiate LPS-induced macrophage activation, an observation consistent with the role of gut-derived bacterial products in exacerbating the hepatic inflammation in NASH (35). Interestingly, we found that URMC099 attenuates macrophage activation induced by both bacterial products and lipotoxic treatment.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We further demonstrated that these CXCL10-enriched EVs are biologically active and are a very potent inducer of macrophage chemotaxis (23). In the current study, we extend these observations to show that the lipotoxic mediator LPC can activate macrophages, as well as potentiate LPS-induced macrophage activation, an observation consistent with the role of gut-derived bacterial products in exacerbating the hepatic inflammation in NASH (35). Interestingly, we found that URMC099 attenuates macrophage activation induced by both bacterial products and lipotoxic treatment.…”
Section: Discussionsupporting
confidence: 84%
“…LPC is the intracellular metabolite of the SFA palmitate; LPC mimics all the cellular toxicity of palmitate (32)(33)(34). We employed lipopolysaccharide (LPS) to simulate the role of gut-derived bacterial products in exacerbating the hepatic inflammation in NASH (35,36). Since proinflammatory signaling often converges on nuclear factor-κB (NF-κB) to induce transcriptional regulation of inflammatory cytokines such as IL-1β (37), we examined macrophage activation under lipotoxic conditions by assessing the mRNA expression of IL-1β and TNF-α in bone marrow-derived macrophages (BMDMs) treated with LPC and LPS with or without URMC099.…”
Section: Urmc099 Treatment In Mice Reduces Ffc-induced Activation Of mentioning
confidence: 99%
“…The gut microbiota consists of bacteria, viruses, fungi, archaea and protozoa rendering the gastro-intestinal tract the most densely colonized microbial community of the human body, with up to 10 14 microbial entities. 97,98 Relevantly, the composition of the gut microbiota is subject to constant fluctuations in time within (intra-) and between (inter-) individuals. Variables responsible for compositional alterations include the host's genome 99,100 and environmental factors such as diet, antibiotics and lifestyle.…”
Section: Lysosomal Function and Its Role In Lipid Metabolism And Inflmentioning
confidence: 99%
“…96 Likewise, an increase of the oxidant-generating enzyme myeloperoxidase was detected both in the liver and in the plasma of obese NASH patients. 97 In spite of the substantial evidence showing increased oxidative stress and the likewise elevation of oxidized fatty acids in NASH patient, it is not yet known to what extent oxLDL itself contributes to this process (and the generation of these oxidized fatty acids). Taking all the current information regarding oxidative stress and disturbed lipid metabolism in NASH into consideration, the specific contribution of oxLDL to NASH should definitely be investigated in more depth, starting by measuring oxLDL levels both in plasma and liver of NASH patients.…”
Section: Oxidized Lipids In Human Nashmentioning
confidence: 99%
See 1 more Smart Citation